Quantitative Analysis for the Delineation of the Subthalamic Nuclei on Three-Dimensional Stereotactic MRI Before Deep Brain Stimulation Surgery for Medication-Refractory Parkinson’s Disease - Su, Chun-Yu; Wong, Alex Mun-Ching; Chang, Chih-Chen; Tu, Po-Hsun; Chen, Chiung Chu; Yeh, Chih-Hua (Frontiers in Human Neuroscience, 2022)
Delineation of the subthalamic nuclei (STN) on MRI is critical for deep brain stimulation (DBS) surgery in patients with Parkinson’s disease (PD). We propose this retrospective cohort study for quantitative analysis of MR signal-to-noise ratio (SNR), contrast, and signal difference-to-noise ratio (SDNR) of the STN on pre-operative three-dimensional (3D) stereotactic MRI in patients with medication-refractory PD. Forty-five consecutive patients with medication-refractory PD who underwent STN-DBS surgery in our hospital from January 2018 to June 2021 were included in this study. All patients had whole-brain 3D MRI, including T2-weighted imaging (T2WI), T2-weighted fluid-attenuated inversion recovery (FLAIR), and susceptibility-weighted imaging (SWI), at 3.0 T scanner for stereotactic navigation. The signal intensities of the STN, corona radiata, and background noise were obtained after placing regions of interest (ROIs) on corresponding structures. Quantitative comparisons of SNR, contrast, and SDNR of the STN between MR pulse sequences, including the T2WI, FLAIR, and SWI. Subgroup analysis regarding patients’ sex, age, and duration of treatment. We used one-way repeated measures analysis of variance for quantitative comparisons of SNR, contrast, and SDNR of the STN between different MR pulse sequences, and we also used the dependent t-test for the post hoc tests. In addition, we used Mann–Whitney U test for subgroup analyses. Both the contrast (0.33 ± 0.07) and SDNR (98.65 ± 51.37) were highest on FLAIR (all p < 0.001). The SNR was highest on SWI (276.16 ± 115.5), and both the SNR (94.23 ± 31.63) and SDNR (32.14 ± 17.23) were lowest on T2WI. Subgroup analyses demonstrated significantly lower SDNR on SWI for patients receiving medication treatment for ≥ 13 years (p = 0.003). In conclusion, on 3D stereotactic MRI of medication-refractory PD patients, the contrast and SDNR for the STN are highest on FLAIR, suggesting the optimal delineation of STN on FLAIR.